Controlled neuronal cell patterning and guided neurite growth on micropatterned nanofiber platforms. (19th October 2015) - Malkoc, Veysi; Gallego-Perez, Daniel; Nelson, Tyler; Lannutti, John J; Hansford, Derek J
Abstract: Patterning neuronal cells and guiding neurite growth are important for applications such as prosthetics, cell based biosensors, and tissue engineering. In this paper, a microdevice is presented that provides neuronal cell patterning and guided neurite growth on a collagen coated gelatin/PCL nanofiber mat. The pattern consisted of a grid of polystyrene microwells/nodes to confine the cell bodies and orthogonal grooves to guide neurite growth from each node. Vacuum assisted cell seeding was used to localize cell bodies in the microwells and physically separate the cells during seeding. The electrospun nanofiber mats under the polystyrene microstructures were coated with collagen to enhance the cellular attachment and enhance differentiation. We evaluated the performance of our device using adhesion, viability, and differentiation assays of neuron-like PC12 cells compared to controls for vacuum seeding, spatial isolation and guidance, and collagen coating of the fibers. The device provided PC12 cell patterning with increased adhesion, differentiation, and guided neurite outgrowth compared to controls, demonstrating its potential for in vitro neuronal cell patterning studies.